Nematode associates and susceptibility of a protected slug (Geomalacus maculosus) to four biocontrol nematodes. Issue 2 (1st February 2017) - Carnaghi, Manuela; Rae, Robbie; De Ley, Irma Tandingan; Johnston, Erin; Kindermann, Gesche; Mc Donnell, Rory; O'Hanlon, Aidan; Reich, Inga; Sheahan, Jerome; Williams, Christopher D.; Gormally, Michael J.
ABSTRACT: The impact of selected entomopathogenic nematodes and Phasmarhabditis hermaphrodita on the European-Union-protected slug Geomalacus maculosus and the sympatric Lehmannia marginata was investigated. There was no significant difference in mortality between slugs treated with nematodes and their controls. The presence of P. hermaphrodita in two G. maculosus cadavers may be the result of necromenic behaviour. This study constitutes the first record of P. californica in Europe.